Kill Castro - Workman, Chuck; Whitman, Stuart; Vaughn, Robert, 1932-; Jack White Productions; Key West Productions; Cinetel Films ([United States] : Key West Productions, 1980)
Stuart Whitman stars as a mercenary hired to kill the Cuban dictator. He soon discovers that he will be immediately expendable once the deed is done. --
Stuart Whitman, Caren Kaye, Robert Vaughn, Woody Strode, Albert Salmi, Michael Gazzo, Raymond St. Jacques, Edward Bell, Sybil Danning, Marie-Louise Gassen.
Director of photography, Robert Carras; editor, James R. Symons; music, Jack White.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 7, 2015)
Keywords: Castro, Fidel, -- 1926- -- Assassination attempts -- Drama; Cuba -- Social conditions -- 1959-1990 -- Drama; Thrillers (Motion pictures); Feature films; Internet videos; Streaming video